Inclusion-Based Community Counseling as an Effort to Strengthen the Resilience of Students with Disabilities at UIN Sunan Gunung Djati Bandung - Eryanti Nurmala Dewi; Aep Kusnawan; Sugandi Miharja (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Students with disabilities face various psychosocial challenges on campus that can impact their resilience. Therefore, an inclusive, community-based mentoring approach is needed. This study aims to examine inclusion-based community counseling as an effort to strengthen the resilience of students with disabilities at UIN Sunan Gunung Djati Bandung. This research uses a conceptual approach by examining the theories of community counseling, inclusion, and resilience in the context of Islamic higher education. The results indicate that inclusion-based community counseling plays a role in strengthening social support, increasing the participation of students with disabilities, and building a welcoming and equitable campus environment. The integration of Islamic values ​​such as mercy and ta'awun strengthens the implementation of humanistic and sustainable community counseling.